The Surgical Apgar Score - Elliot Pittman, BSc (Pharm), PharmD, MD; Elijah Dixon, BSc, MSc (Epi), MD, FRCSC, FACS; Kaylene Duttchen, BSc (Pharm), MD, FRCPC (Annals of Surgery Open, 2022)
Objectives:. To review the current literature evaluating the performance of the Surgical Apgar Score (SAS). Background:. The SAS is a simple metric calculated at the end of surgery that provides clinicians with information about a patient’s postoperative risk of morbidity and mortality. The SAS differs from other prognostic models in that it is calculated from intraoperative rather than preoperative parameters. The SAS was originally derived and validated in a general and vascular surgery population. Since its inception, it has been evaluated in many other surgical disciplines, large heterogeneous surgical populations, and various countries. Methods:. A database and gray literature search was performed on March 3, 2020. Identified articles were reviewed for applicability and study quality with prespecified inclusion criteria, exclusion criteria, and quality requirements. Thirty-six observational studies are included for review. Data were systematically extracted and tabulated independently and in duplicate by two investigators with differences resolved by consensus. Results:. All 36 included studies reported metrics of discrimination. When using the SAS to correctly identify postoperative morbidity, the area under the receiver operating characteristic curve or concordance-statistic ranged from 0.59 in a general orthopedic surgery population to 0.872 in an orthopedic spine surgery population. When using the SAS to identify mortality, the area under the receiver operating characteristic curve or concordance-statistic ranged from 0.63 in a combined surgical population to 0.92 in a general and vascular surgery population. Conclusions:. The SAS provides a moderate and consistent degree of discrimination for postoperative morbidity and mortality across multiple surgical disciplines.